2022
DOI: 10.3390/ijgi11110555
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Externalities, Network Externalities and Urban High-Quality Development: A Case Study of Urban Agglomeration in the Middle Reaches of the Yangtze River

Abstract: The rapid development of the urban network has led to the fact that cities are no longer single individuals, and the network has changed the urban development environment. The interaction between cities has gradually become an important factor for the high-quality development (HQD) of cities. From the perspective of externalities, it is of great significance to explore the impact of agglomeration externalities and network externalities on the HQD of cities to promote the high-quality and sustainable developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Firstly, the relative price variance of commodity market in Ningzhenyang is calculated by using the consumer price index of eight kinds of commodities, such as food, tobacco, alcohol and clothing, and referring to the relative price model in Li et al,8 as is shown in Figure 2. Secondly, capital, land and labor are chosen as three factors of production, and then the price variance of factor market in Ningzhenyang is calculated by using fixed asset investment price index, real estate price index, land price index and labor price index, respectively, which is shown in Figure 3.…”
Section: Evaluation Of Market Integrationmentioning
confidence: 99%
“…Firstly, the relative price variance of commodity market in Ningzhenyang is calculated by using the consumer price index of eight kinds of commodities, such as food, tobacco, alcohol and clothing, and referring to the relative price model in Li et al,8 as is shown in Figure 2. Secondly, capital, land and labor are chosen as three factors of production, and then the price variance of factor market in Ningzhenyang is calculated by using fixed asset investment price index, real estate price index, land price index and labor price index, respectively, which is shown in Figure 3.…”
Section: Evaluation Of Market Integrationmentioning
confidence: 99%
“…It is the time-space compression effect brought about by the transportation revolution that has brought cities closer together and made the global flow of factors possible. Although the theory of space of flow challenges the distance-decaying nature of traditional space, it has been demonstrated that distance decay continues to exist for both material inter-city trips and immaterial mobile communications [55][56][57].…”
Section: Research Hypothesismentioning
confidence: 99%
“…Their research collectively affirmed that AEs considerably advance economic growth. Contrarily, Liu et al [9] found that AEs' impact on high-quality development unfolds as a U-shaped relationship, thereby implying that such externalities initially impede, but subsequently enhance, high-quality development. Regarding innovation, studies conducted by Yang et al [10], Yao and Wu [11], and Li and Song [12], using spatial econometric models, underscored that AEs can notably foster innovation development in Chinese cities.…”
Section: Introductionmentioning
confidence: 99%